2020
DOI: 10.3390/pathogens9030161
|View full text |Cite
|
Sign up to set email alerts
|

Isoalantolactone Enhances the Antimicrobial Activity of Penicillin G against Staphylococcus aureus by Inactivating β-Lactamase during Protein Translation

Abstract: β-Lactamase-positive Staphylococcus aureus is one of the most prevalent multidrug-resistant pathogens worldwide and is associated with increasing threats to clinical therapeutics and public health. Here, we showed that isoalantolactone (IAL), in combination with penicillin G, exhibited significant synergism against 21 β-lactamase-positive S. aureus strains (including methicillin resistant S. aureus). An enzyme inhibition assay, a checkerboard minimum inhibitory concentration (MIC) assay, a growth curve assay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Furthermore, it could recently be shown that IAL synergistically increased the antimicrobial effects of penicillin G against S. aureus by inactivating β-lactamase. Thus, a therapy of combined IAL and penicillin G demonstrated equal effects compared with sulbactam with penicillin G [ 184 ]. These findings suggested that IAL—in combination with β-lactam antibiotics—may be a promising drug in the treatment of S. aureus pneumonia [ 183 , 184 ].…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it could recently be shown that IAL synergistically increased the antimicrobial effects of penicillin G against S. aureus by inactivating β-lactamase. Thus, a therapy of combined IAL and penicillin G demonstrated equal effects compared with sulbactam with penicillin G [ 184 ]. These findings suggested that IAL—in combination with β-lactam antibiotics—may be a promising drug in the treatment of S. aureus pneumonia [ 183 , 184 ].…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…Thus, a therapy of combined IAL and penicillin G demonstrated equal effects compared with sulbactam with penicillin G [ 184 ]. These findings suggested that IAL—in combination with β-lactam antibiotics—may be a promising drug in the treatment of S. aureus pneumonia [ 183 , 184 ]. Furthermore, it could be shown that low micromolecular concentrations (1–20 µM) of ALT intensified the uptake of S. aureus and thus stimulated immune functions of macrophages [ 185 ].…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…The β-lactamase activity was detected using nitrocefin as described previously ( Zhou et al., 2020 ). In this study, it was first determined that CA inhibited the activity of KPC-2 during bacterial growth and in unprocessed culture supernatants.…”
Section: Methodsmentioning
confidence: 99%
“…Isoalantolactone showed synergistic effects against 21 β-lactamase-positive S. aureus strains (including methicillin-resistant S. aureus , when combining with penicillin G). The association of drugs was also effective on S. aureus -infected mice, increasing the survival rate (88.24%) after 144 h treatment [ 87 ].…”
Section: Biological Activitymentioning
confidence: 99%